2022
DOI: 10.7759/cureus.23384
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Fat Embolism Syndrome Masquerading as COVID-19 Pneumonia

Abstract: In the wake of the novel coronavirus disease 2019 (COVID-19) pandemic and its associated mortality and virulence, a high clinical suspicion must be maintained for all patients presenting with respiratory failure. However, there are well-known disease processes that may have a similar presentation. We present a case of a 25-year-old male who suffered a right tibia fracture after a motor vehicle collision. He had acute hypoxic respiratory failure within 24 hours of admission, requiring mechanical ventilation. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Interestingly, Colleluori et al 12 observed a pathophysiological process with fat embolism in association with SARSCoV‐2 infection resembling FES. Misdiagnosis of FES as COVID‐19 infection, therefore, is not surprising because of a similar clinical and radiological picture, and was indeed reported in two patients with FES in association with bone fractures 13,14 . In our patient, however, COVID‐19 infection was ruled out early by a negative PCR for SARSCoV‐2.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Interestingly, Colleluori et al 12 observed a pathophysiological process with fat embolism in association with SARSCoV‐2 infection resembling FES. Misdiagnosis of FES as COVID‐19 infection, therefore, is not surprising because of a similar clinical and radiological picture, and was indeed reported in two patients with FES in association with bone fractures 13,14 . In our patient, however, COVID‐19 infection was ruled out early by a negative PCR for SARSCoV‐2.…”
Section: Discussionsupporting
confidence: 79%
“…Misdiagnosis of FES as COVID-19 infection, therefore, is not surprising because of a similar clinical and radiological picture, and was indeed reported in two patients with FES in association with bone fractures. 13,14 In our patient, however, COVID-19 infection was ruled out early by a negative PCR for SARSCoV-2.…”
Section: Discussionmentioning
confidence: 74%